التكييف الفقهي والقانوني لوقف العقود - د. الغزالي محمد محمد الحسن (White Nile Journal for Studies and Research, 2018)
This Study aims to (find out) the juristic adaptation of legal ceasing of contracts, after going back to the Islamic Juristic opinions and the opinion of the Civil law in this matter: The researcher followed the inductive static method in tracing the five research steps and The Study reached a number of results the nemeses one: is The ceased contract remains right, but it should be accepted, The Islamic Juristic, gave the right to a judge to cease the contract till it be accepted by the legal authorities this, what followed by the civil law. Finally and according to the result's in lights and discussion, the researchers suggested some recommendations.